Survey of Social Sciences Graduates 2007 - NIHERST (NIHERST, 2008)
This study covered 1,646 Trinidad and Tobago nationals who graduated from the Faculty of Social Sciences. The University of the West Indies (UWI) over the period 2001-2005. It was designed to obtain information on the current status of the Social Sciences graduates. Data were collected on the following characteristics: gender, age, area of specialization, employment/underemployment, length of time taken to acquire first job, sector of employment, income levels, job satisfaction, relevance of academic qualifications, and the number of graduates pursuing further education. Key indicators of job mobility and migration were also monitored.
Keywords: Social Sciences